2018
DOI: 10.1128/msphere.00534-18
|View full text |Cite
|
Sign up to set email alerts
|

The Buoyancy of Cryptococcus neoformans Is Affected by Capsule Size

Abstract: The buoyancy of a microbial cell is an important physical characteristic that may affect its transportability in fluids and interactions with tissues during infection. The polysaccharide capsule surrounding C. neoformans is required for infection and dissemination in the host. Our results indicate that the capsule has a significant effect on reducing cryptococcal cell density, altering its sedimentation in seawater. Modulation of microbial cell density via encapsulation may facilitate dispersal for other impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…MS or V8 medium were used for induction of mating and prepared as described previously [38]. DME medium, minimal medium (MM), and RPMI-contaning medium were used for the induction of Cryptococcus capsule formation [39][40][41]. All other media used in this study were prepared as previously described [39].…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…MS or V8 medium were used for induction of mating and prepared as described previously [38]. DME medium, minimal medium (MM), and RPMI-contaning medium were used for the induction of Cryptococcus capsule formation [39][40][41]. All other media used in this study were prepared as previously described [39].…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…The GalXM consists of an α-(1 → 6)-galactan backbone with galactomannan side chains that are further substituted with variable numbers of xylose and glucuronic acid residues (1). It has recently been characterized that the polysaccharide capsule can function as a flotation device to facilitate transport and dispersion in aqueous fluids (2).…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that titanization is triggered by exposure to components of the bacterial cell wall (9), while interactions between bacteria and the capsule have previously been described (63,64). Capsule also contributes to the buoyancy of Cryptococcus cells (65). As such, the importance of redistributing capsular epitopes during titanization should be considered in the context of Cryptococcus cell biology both in the environment and during infection.…”
Section: Discussionmentioning
confidence: 99%